Wanita Dan Kepemimpinan (Studi kasus terpilihnya kepala desa wanita di desa jangrana, Kecamatan Kesugihan, Kabupaten Cilacap) - Martomo, Yitno Puguh (Responsibilitas, 2010)
This research is to describe the emergence of women leaders and more emphasis on research prototype descriptive as well as qualitative research as well as field research. So this study will not test hypotheses but simply presents the results of research in the field. This research also to conculded that the village head jangrana is a leader who emerged from genetic factors and social factors can thus be said that ecological factors are factors that are owned by the emergence of leaders of the village head. Conclusion is jangrana mayor also has the ability to influence and persuade people jangrana Village, District Kesugihan, Cilacap regency. Keywords: Pemimpin, Kepemimpinan, Wanita.